Respuesta :
First we write both functions:
f (x) = x ^ 2 - 3x + 3
g (x) = ((x-1) / (4))
We now make the composition of functions:
f (g (x)) = ((x-1) / (4)) ^ 2 - 3 (((x-1) / (4))) + 3
We now evaluate for x = 5:
f (g (5)) = ((5-1) / (4)) ^ 2 - 3 (((5-1) / (4))) + 3
f (g (5)) = 1
Answer:
f (g (5)) = 1
f (x) = x ^ 2 - 3x + 3
g (x) = ((x-1) / (4))
We now make the composition of functions:
f (g (x)) = ((x-1) / (4)) ^ 2 - 3 (((x-1) / (4))) + 3
We now evaluate for x = 5:
f (g (5)) = ((5-1) / (4)) ^ 2 - 3 (((5-1) / (4))) + 3
f (g (5)) = 1
Answer:
f (g (5)) = 1